Electrochemical behavior of Ti and Ti6Al4V in aqueous solutions of citric acid containing halides - Anelise Marlene Schmidt (Materials Research, 2006)
This paper reports on an investigation of the electrochemical behavior of Ti grade 2 and Ti6Al4V alloy in aqueous citric acid solutions with pH 2.0 containing halide ions. Voltammetric studies of Ti and the alloy in citric acid, with and without chloride ions, indicate that the Ti and Ti alloy presented a passive behavior in the test solutions used. Pitting was observed at 3.0 and 2.5 V/SCE for Ti and Ti6Al4V, respectively, when bromide ions were added to the solution. In solutions containing fluoride ions, dissolution of the film occurred at potentials close to - 1.0 V/SCE in both electrodes. The iodide ions oxidized on the passive oxide film at potentials close to 1.0 V/SCE. EIS results of the materials in citric acid solutions containing chloride ions revealed that the film's resistance increased as the applied potential rose from 0 to 1.0 V. In bromide-containing solutions, breakdown of the film was confirmed at potentials above 2.0 V/SCE in both electrodes. These results suggest film reformation for Ti and the alloy in solutions containing fluoride at potentials within the passive region.